From Active‐Site Models to Real Catalysts: Importance of the Material Gap in the Design of Pd Catalysts for Methane Oxidation. Issue 9 (10th May 2017) - Doan, Hieu A.; Sharma, Munish K.; Epling, William S.; Grabow, Lars C.
Abstract: The front cover artwork for Issue 9/2017 is provided by the University of Houston. The image shows the charge density difference in the transition state of methane activation over a single crystal Pd(1 0 0) surface as obtained from electronic structure simulations. See the Full Paper itself at https://doi.org/10.1002/cctc.201601333 . Abstract : "The localization of charge‐density changes is ultimately responsible for promoting or inhibiting CH4 activation on Pd‐based catalysts" This and more about the story behind the research featured on the front cover can be found in this issue's Cover Profile. Read the full text of the corresponding research athttps://doi.org/10.1002/cctc.201601333 .